Specification for control switches (switching devices, including contactor relays, for control and auxiliary circuits, for voltages up to and including 1000 V a.c. and 1200 V d.c.). Indicator lights. Standardization of fixing hole of single hole mounted push-buttons and indicator lights Part 2 Sections 2.5 and 2.6, (31st May 1978) - British Standards Institution,
No abstract available